2018
DOI: 10.1111/exd.13437
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐inflammatory effect of astaxanthin in phthalic anhydride‐induced atopic dermatitis animal model

Abstract: In this study, we investigated anti-dermatitic effects of astaxanthin (AST) in phthalic anhydride (PA)-induced atopic dermatitis (AD) animal model as well as in vitro model. AD-like lesion was induced by the topical application of 5% PA to the dorsal skin or ear of Hos:HR-1 mouse. After AD induction, 100 μL of 1 mg/mL and 2 mg/mL of AST (10 μg or 20 μg/cm ) was spread on the dorsum of ear or back skin three times a week for four weeks. We evaluated dermatitis severity, histopathological changes and changes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 62 publications
1
44
0
3
Order By: Relevance
“…We showed that astaxanthin inhibited cigarette smoke-induced inflammatory cell infiltration in BALF. Although Nrf2 suppresses inflammation as a secondary consequence of its antioxidant effect, astaxanthin has been also reported to directly suppress inflammation [44,45]. The suppression of inflammatory cell infiltration in BALF may also be related to this property of astaxanthin.…”
Section: Discussionmentioning
confidence: 99%
“…We showed that astaxanthin inhibited cigarette smoke-induced inflammatory cell infiltration in BALF. Although Nrf2 suppresses inflammation as a secondary consequence of its antioxidant effect, astaxanthin has been also reported to directly suppress inflammation [44,45]. The suppression of inflammatory cell infiltration in BALF may also be related to this property of astaxanthin.…”
Section: Discussionmentioning
confidence: 99%
“…AD is a chronic inflammatory skin disease associated with various factors, including immunological abnormalities that contribute to the pathogenesis and development of skin lesions. A recent report showed that ASX inhibited the gene expression of several proinflammatory biomarkers such as interleukin-1β (IL-1β), interleukin-6 (IL-6), and tumor necrosis factor-α (TNF-α) in an AD animal model [ 31 ]. Several investigators examined the inhibition of nuclear factor-kappa B (NF-κB) by ASX.…”
Section: Skin-protective Mechanisms Of Astaxanthinmentioning
confidence: 99%
“…Astaxanthin has a variety of biological activities, such as a wound healing effects on full-thickness dermal wounds in mice [ 10 ], inhibitory effects on age-related skin deterioration and maintenance effect on skin conditions associated with environmentally induced damage [ 11 ], preventive effects against renal tubular oxidative damage [ 12 ], protective effects of astrocytes against trauma-induced apoptosis through the inhibition of NKCC1 expression via the NF-κB signaling pathway [ 13 ], and neuroprotective effects in a rat model of spinal cord injury [ 14 ]. Furthermore, previous studies have also shown that astaxanthin has an anti-inflammatory effect in the phthalic anhydride-induced atopic dermatitis animal model [ 15 ].…”
Section: Introductionmentioning
confidence: 99%